Radiometric study and associated radiological hazards in soil near the Bheramara 410 MW Combined Cycle Power Plant, Kushtia, Bangladesh - Siraz, M. M. Mahfuz; Islam, Rajikul; Shelley, Afroza; Mahmud, Araf; Alam, Mohammad Shafiqul; Rashid, Md. Bazlar; Khandaker, Mayeen Uddin; Osman, Hamid; Yeasmin, Selina (Isotopes in environmental and health studies, 2025)
This pioneering study assesses the radiological risk of naturally occurring radionuclides in soil around the Bheramara 410 MW Combined Cycle Power Plant (natural gas and high-speed diesel) in Kushtia, Bangladesh. Thirty soil samples were collected at radial distances of 50 m, 500 m, 1000 m, and 3000 m from the plant, these distances were strategically selected to represent immediate proximity (50 m), near-field (500 m), mid-range (1000 m), and far-field (3000 m) zones, enabling a gradient analysis of potential radiological impact. Using high-purity germanium (HPGe) gamma-ray spectrometry, the activity concentrations of Ra, Th, and K were found to range from 20 ± 2 to 28 ± 3 Bq/kg, 25 ± 2 to 41 ± 4 Bq/kg, and 310 ± 21 to 440 ± 34 Bq/kg, respectively. While Ra concentrations were below the global average (30 Bq/kg), some measured values of Th exceeded the global average of 35 Bq/kg, and K concentrations in certain samples were higher than the global average of 400 Bq/kg. No detectable Cs was observed, confirming no artificial contamination. Radiological hazard indices such as radium equivalent activity (mean: 100.60 Bq/kg), outdoor absorbed dose rate (mean: 48.56 nGy/h), outdoor annual effective dose (mean: 0.06 mSv/year), external hazard index (mean: 0.27), gamma representative level index (mean: 0.74), and excess lifetime cancer risk (mean: 0.22 × 10 ) were all within recommended safety limits. Various statistical analyses, including descriptive statistics, Pearson correlation, principal component analysis (PCA), and hierarchical cluster analysis (HCA), were performed and these revealed that Ra and Th were the main contributors to radiological risk, while K showed weaker associations. The findings suggest that the soil is safe for agricultural and construction use, but routine monitoring is recommended to ensure environmental protection. This study provides essential baseline data and analytical insight into radiological risk management in power generation industrial regions of Bangladesh.